2019
DOI: 10.1111/jdv.15903
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the influence of partial biopsy of primary melanoma on disease recurrence and patient survival

Abstract: Background Complete surgical excision is the preferred biopsy type for suspicious melanocytic lesions. However, partial biopsy is sometimes used in special situations. Previous studies have explored the effect of partial biopsy of a primary melanoma on patient outcome with controversial results. Objective We performed a meta‐analysis on the influence of the type of biopsy of a primary melanoma on recurrence‐free survival (RFS) and melanoma‐related survival (MRS). Methods Clinical trials, observational cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…12,13 A survey of family physicians in southwestern Ontario showed that if an excisional biopsy could not be performed, one-half of respondents would perform an incisional biopsy. 14 There is no evidence that incisional biopsy has an adverse effect on the prognosis of patients by transferring melanoma cells to skin lymphatics or blood vessels, 1,15,16 but incisional biopsy may affect the histological evaluation. Ng et al 17 found that up to 20% of initial partial biopsies were misleading because they underestimated the final Breslow depth of the melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A survey of family physicians in southwestern Ontario showed that if an excisional biopsy could not be performed, one-half of respondents would perform an incisional biopsy. 14 There is no evidence that incisional biopsy has an adverse effect on the prognosis of patients by transferring melanoma cells to skin lymphatics or blood vessels, 1,15,16 but incisional biopsy may affect the histological evaluation. Ng et al 17 found that up to 20% of initial partial biopsies were misleading because they underestimated the final Breslow depth of the melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Partial biopsies are not recommended and should be reserved for circumstances where a complete EB is impracticable [ 9 ]. The most common scenario where a partial biopsy is necessary is when the patient has a large lesion on the head, neck, hands, feet, anterior legs or genitalia.…”
Section: Biopsy Techniquementioning
confidence: 99%
“…no visible tumour cells in the specimen margins upon histopathological examination ( 6 – 9 ). Although a recent meta-analysis has shown that incomplete excisions and partial punch biopsies of melanomas prior to their complete removal do not increase the recurrence risk or decrease survival rates ( 12 ), incompletely excised melanocytic lesions with any suspicion of melanoma should be considered a treatment failure. An incomplete excision of a non-dysplastic or low-grade dysplastic naevus does not require a re-excision ( 13 ), but if the patient develops a recurrent naevus it may mimic melanoma and lead to diagnostic difficulties in the future, as well as unnecessary re-excisions ( 14 , 15 ).…”
mentioning
confidence: 99%